Defence by Deprivation in the Personal Sponsorship Contract : A Comparative Study - Jazea, Hussein; Ali, Raqiya (Journal of Legal Sciences, 2023)
The payment of stripping is more prominent than the defenses that the personal guarantor can hold against the creditor; In order for him to maintain the financial guarantee, and the guarantor derives this payment from the personal guarantee, i.e. not a connection with the guarantee. Your educational tutorial, environmental protection plans, environmental protection plans, environmental protection plans, environmental protection plans, Guaranteeing him to pay the guarantor towards the creditor by stripping the money burdened with in-kind insurance as security for the debt he is guaranteed; If this insurance was prior or contemporary to the personal guarantee, and what distinguishes this special form of payment by abstraction from the general rule for it, it does not bear the costs of payment by abstraction, unlike the general rule for payment by abstraction that pays that.